Screening aptamers for 5-hydroxytryptamine receptor and its anti-depressant function - SHAO Zhi-ding, GAO Xue, REN Jing, TANG Xiao-lei (Jichu yixue yu linchuang, 2022)
Objective To explore the potential anti-depression effect of the screened nucleic acid aptamers via blocking 5-HT re-uptake binding to the 5-HTR. Methods The mouse gene coding 5-HT1AR was cloned, constructed, and the recombinant 5-HT1AR was expressed and purified. The ssDNA aptamer that binds 5-HT1AR specifically was screened by SELEX. The binding sites and binding affinity of ssDNA were measured. At the same time, ssDNA aptamer inhibitory protein uptake and the effect against depression were verified at cellular level and mouse depression model. Results The pET28a-5-HT1AR plasmid was successfully cloned and constructed. The pET28a-5-HT1AR protein was purified by 6× His label after transfected into E.coli DH5ɑ. The protein was consistent with mouse 5-HT1AR by peptide fingerprint analysis. After 12 rounds of positive screening and 5 rounds of negative screening, four aptamers with high affinity and high specificity were obtained and the same epitope was bounded by four aptamers shown by results of enzyme-linked oligonucleotide assay(ELONA).The 5-HT uptake was influenced by aptamer 18 in vitro, and the improvement of depression state after intravenous injection of aptamer 18 was proved by the tail suspension experiment in mice. Conclusions Aptamer for 5-HTR is expected to be a new type of antidepressant used in the treatment of clinical depression. And this research also might provide a novel tool for screening of small molecule antagonist.